An approach to the application of knowledge management in the Judicial Power - Pacheco Huancas, Iris Estela (2009)
At present, knowledge management is a powerful tool for change and innovation in any type of organization, whether private or public. In this article, knowledge management proposes the creation, organization, renewal, transmission and use of the knowledge gained along the years by the justices and jurisdictional personnel of the Judiciary who have imparted justice based on their specific needs. The implementation of information technology and knowledge management in the judicial environment would facilitate and promote permanent learning within the institution to achieve promptness, certainty and predictability in the solution of legal conflicts.